Redistribution across Europe: How much and to whom? - Bernhard Hammer; Michael Christl; Silvia De Poli (European Commission, Joint Research Centre (JRC), 2021)
Governments face a potential trade-off between provision for the growing population in retirement and the support of working-age households with low income. Using EUROMODbased microdata from 28 countries, we (a) quantify the redistribution to the pensioner and non-pensioner populations, (b) study the position of net beneficiaries in the overall income distribution and (c) analyse how taxes and benefits affect the working-age population with low income. Our results provide novel insights into the distributive role of tax-benefit systems across Europe. Interestingly, a strong overall redistribution between households is associated with generous pensions for a portion of the retirees but negatively related to support for low-income households.
Keywords: 330; Redistribution; Welfare state; Inequality; Microsimulation; EUROMOD